Legal Protections of Pratama Clinic Doctors in Providing Aesthetic Services - Lenno Idjianto; I Nyoman Suyatna; Ika Widi Astuti (Journal of Law, Politic and Humanities, 2025)
Pratama clinic is a facility that provides limited medical services carried out by a doctor or dentist with technical responsibility. This research uses a type of normative legal research, namely deductively starting with an analysis of articles in statutory regulations and their relationship to their application in practice. The results of this research are that currently, the regulatory framework relating to medical aesthetics in Indonesia does not have formal regulations. Regulations regarding medical aesthetics refer to several regulations regarding related medical services and can be used as a legal basis for medical aesthetics. Legal protection for aesthetic doctors operating in beauty clinics is currently regulated by Law Number 29 of 2004 concerning Medical Practice. This law provides legal protection for doctors who comply with professional standards and standard operational processes when practicing.